Pediatric Eye-Related Emergency Department Visits and Pediatric Eye Provider Location and Density - Julius T. Oatts, MD; Albert Xu, BS; Jonathan R. Morse, BA; John M. Nesemann, MD; Kara M. Cavuoto, MD; Jeremy D. Keenan, MD (Ophthalmology Science)
Objective: There is a shortage of pediatric eye specialists. Inaccessible eye care may lead parents to bring their children to the emergency department (ED) to address eye problems that could have been handled at a clinic visit. This study aimed to determine the association between childhood eye-related ED visits and the location and density of pediatric eye specialists in California. Design: A population-based cross-sectional study. Participants: All California ED visits between January 2012 and December 2021 for patients ≤18 years of age were identified using the California Office of Health Care Access and Information Database. Methods: International Classification of Diseases diagnosis codes were used to identify eye-related ED visits. Public databases were used to identify pediatric ophthalmologist and optometrist addresses. Census data were used to determine the number of visits per 10 000 children in each zip code. Poisson regressions evaluated associations at the zip code level of eye-related ED visits and provider density with geographic sociodemographic factors. Main Outcome Measures: Incidence of pediatric eye-related ED visits. Results: Of the 117 363 721 ED visits in California between 2012 and 2021, 27 346 729 (23.3%) were for children, of which 391 985 (1.4%) were eye-related. Median age was 5.0 years (interquartile range: 2.0, 10.0), and 51.7% were male. The most common diagnoses were conjunctivitis (250 028; 63.8%), chalazion/blepharitis (56 389; 14.4%), and other disorders of the eye/adnexa (13 070; 3.3%). The mean number of visits per year per 10 000 children was 43 ± 12 (median 46, interquartile range: 43, 51). The estimated number of pediatric eye providers in California in 2023 was 142 (1 per 61 413 children). Zip codes with more pediatric eye providers had fewer eye-related ED visits: each additional provider per 10 000 children was associated with 2.1 fewer eye-related ED visits per 10 000 children (95% confidence interval −0.04 to −4.25; P = 0.046). Conclusions: Most eye-related ED visits were for nonemergent eye conditions. There was a low eye provider-to-child ratio and an association between provider density and eye-related ED visit incidence. Expanding pediatric eye care could improve access and decrease ED utilization for nonemergent eye concerns. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.